A feminist interview?: Intersubjectivity in an ethnography on gender inequalities in the social sciences - Lube Guizardi, Menara (2025)
This article analyses the construction of an intersubjective methodological strategy for an ethnographic project on gender inequalities in the social sciences. Composing the main qualitative instrument –the interview script to be used with female researchers– was a transcendent learning experience. We approach this analytical process by reflecting on the negotiation of the interviews as part of a feminist ethnography. To do so, we synthesise what we understand by feminist ethnography, delving into criticism of the interview as a tool. Then, we narrate the process of formulating the interview script, explaining the research team’s susceptibilities, and our decision to interview our team members before heading into the field. In addition, we explore the reflections and analyses undertaken in weekly workshops conducted with a feminist therapist. Finally, we conclude by reflecting on the limits and possibilities of (self)recognition in the methodology adopted.